The Effectiveness of UNM Public Relations in Disseminating Information to the Academic Community - Agatoni Buttang; Sirajuddin Saleh; Risma Niswaty (Jurnal Ad'ministrare, 2023)
In achieving academic success, students need to understand the academic requirements, policies, extracurricular activities, internship or career opportunities, and procedures that apply at the college. Effective and regular information helps academics gather the necessary information and maximize their experience in higher education. This not only enriches the community experience but also builds social, academic, and professional ties. This research is a qualitative descriptive study that aims to determine the effectiveness of UNM Public Relations in disseminating information to the academic community. So that this goal can be achieved, researchers use data collection techniques through interviews, observation, and documentation. There were nine informants in this study. The data analysis technique in this research consists of four activity flows, namely: data collection, data presentation, data condensation, and drawing conclusions. The results of research using five indicators show that UNM Public Relations is declared effective in providing information because the academic community has confidence in the competence of UNM Public Relations and the veracity of the information published. However, there are deficiencies in indicators of consistency and sustainability of UNM Public Relations in providing information. The content of the information presented does not fully meet the needs of the academic community. Therefore, UNM Public Relations needs to increase the use of various channels in disseminating information. This research highlights the use of new communication methods that have not yet been used by UNM Public Relations. For example, the use of social media, digital platforms, or other communication tools that can expand the reach of information. This research provides data regarding the extent to which the information conveyed by UNM Public Relations reaches the academic community. This can provide deeper insight into how effective PR efforts are in disseminating information. This research can identify inhibiting and encouraging factors. Based on the findings of this research, recommendations were produced for improving and developing UNM Public Relations